Differences in Multidisciplinary and Interdisciplinary Treatment Programs for Fibromyalgia: A Mapping Review - Emanuele Maria Giusti; Gianluca Castelnuovo; Enrico Molinari (Pain Research and Management)
Fibromyalgia is a multifaceted chronic pain syndrome and the integration of different health disciplines is strongly recommended for its care. The interventions based on this principle are very heterogeneous and the difference across their structures has not been extensively studied, leading to incorrect conclusions when their outcomes are pooled. The objective of this mapping review was to summarize the characteristics of these programs, with particular focus on the integration of their components. We performed a search of the literature about treatments for fibromyalgia involving multiple disciplines on PubMed and Scopus. Starting from 560 articles, we included 22 noncontrolled studies, 10 controlled studies, and 17 RCTs evaluating the effects of 38 multidisciplinary or interdisciplinary interventions. The average quality of the studies was low. Their outcomes were usually pain intensity, quality of life, and psychological variables. We created a map of the programs based on the degree of integration of the included disciplines, which ranged from a juxtaposition of few components to a complex harmonization of different perspectives obtained through teamwork strategies. The rehabilitation programs were then thoroughly described with regard to the duration, setting, therapeutic components, and professionals included. The implications for future quantitative reviews are discussed.